Influence of urea and glucose on corrosion resistance of Gold 21K alloy in the presence of artificial sweat - Babu Mahalakshmi; Venkatachalam Prathipa; Susai Rajendran; Anitha Nilavan (Zaštita Materijala)
Corrosion resistance of Gold 21K alloy immersed in artificial sweat in the absence and presence of 100 ppm of urea and also 100 ppm of D-Glucose has been investigated by polarization study and AC impedance spectra. It is observed that Corrosion resistance of Gold 21K alloy immersed in artificial sweat in the presence of 100 ppm of urea / D-Glucose increases. Hence it is concluded that people wearing ornaments made of Gold 21K alloy need not worry about the excess of urea / D-Glucose in their sweat. When Gold 21K alloy is immersed in artificial sweat in the presence of 100 ppm of urea, Linear Polarisation Resistance value increases from 103389Ohmcm2 to 123437Ohmcm2 ; corrosion current decreases from 4.036 x10-7A/cm2 to 3.308 x10-7A/cm2 ; charge transfer resistance value increases from 10490 Ohmcm2 to 14070 Ohmcm2 ; impedance value increases from 4.253 to 4.324; double layer capacitance decreases from 4.862x10-10 F/cm2 to 3.625x10-10 F/cm2 , and phase angle increases from 38.91 to 70.14. When Gold 21K alloy is immersed in artificial sweat in the presence of 100 ppm of D-Glucose, Linear Polarisation Resistance value increases from 103389Ohmcm2 to 4817257Ohmcm2 ; corrosion current decreases from 4.036 x10-7A/cm2 to 0.161x10-7A/cm2 ; charge transfer resistance increases from 10490Ohmcm2 to 33300Ohmcm2 ; impedance value increases from 4.253 to 4.977; double layer capacitance decreases from 4.862x10-10 F/cm2 to 1.5315x10-10 F/cm2 , and phase angle increases from 38.91° to 79.74°.